IMPROVING THE PERFORMANCE OF THE INSTITUTIONBY USING APRIORI ALGORITHM (International Journal of Engineering Sciences & Management Research, 2017)
Public institutions are units that are set up for public public services. In order to meet the needs of the society and to continue the social life on a regular basis, public services need to be carried out without disruption. Increasing the performance of public institutions will make it easier for the state and for the citizens to do their jobs easily. In this study, it is aimed to increase the performances of institutions by using apriori algorithm which is one of the algorithms for extracting association rules in data mining and to make the work of the citizens faster and easier. Moreover, in this study, the subjects that institutions should work together are observed. It is aimed to accelerate the operation of the institutions and to increase the performances of the personnel by detecting these issues